2021
DOI: 10.1093/aje/kwab019
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Rate of Memory Decline From Mid to Later Life: Evidence From the English Longitudinal Study of Ageing

Abstract: Evidence on the role of early-life adversity in later-life memory decline is conflicting. We investigated the relationships between adverse childhood experiences (ACEs) and memory performance and rate of decline over a ten-year follow-up among mid-to-older adults in England. Data were from biennial interviews with 5,223 participants aged 54+ in the population-representative English Longitudinal Study of Ageing from 2006/07-2016/17. We examined self-reports of nine ACEs prior to age 16, which related to abuse, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 52 publications
4
25
0
Order By: Relevance
“…Two other studies also reported similar findings, of better working memory in adults with a history of adverse/unpredictable childhoods (Mittal et al, 2015;Young et al, 2018). Another large population-based study, the English Longitudinal Study on Ageing (n=5223), did not find any association between ACEs & memory decline (immediate and delayed recall) (O'Shea et al, 2021). A systematic review of studies looking at the association between ACEs and neurocognition in healthy individuals found a high degree of heterogeneity in methods & their findings (Su et al, 2019).…”
Section: Introductionmentioning
confidence: 76%
“…Two other studies also reported similar findings, of better working memory in adults with a history of adverse/unpredictable childhoods (Mittal et al, 2015;Young et al, 2018). Another large population-based study, the English Longitudinal Study on Ageing (n=5223), did not find any association between ACEs & memory decline (immediate and delayed recall) (O'Shea et al, 2021). A systematic review of studies looking at the association between ACEs and neurocognition in healthy individuals found a high degree of heterogeneity in methods & their findings (Su et al, 2019).…”
Section: Introductionmentioning
confidence: 76%
“…To our knowledge, no study has examined the relationship between ACEs and SCD using a representative sample of the US. Prior research examined the relationship between ACEs and objective cognition (Gold et al, 2021; O’Shea et al, 2021), which suggests that adverse experiences in early life contribute to poorer cognitive outcomes as people age. Furthermore, SCD may be an early indicator of cognitive problems and is therefore important to consider in the context of aging and AD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse childhood experiences (ACEs) have been shown to be associated with poorer objective cognition (Gold et al, 2021; O’Shea et al, 2021), but there has been limited research examining ACEs and subjective cognition. Subjective cognitive decline (SCD) refers to the perception of worsening cognitive function or more frequent confusion or memory loss, albeit normal performance on standardized cognitive tests (Jessen et al, 2014; Studart & Nitrini, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…violence in the home, parental addiction, mental illness, or institutionalisation) [ 9 ]. A recent study, using data from the English Longitudinal Study of Ageing (ELSA), demonstrated a mild association between ACEs and memory decline over ten years from middle to older age [ 10 ]. Memory, processing speed, and executive function deficits have also been associated with ACE exposure among middle-aged adults with depression [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%